A Critical Analysis of Systemic Influences on Spiritual Development for LGBTQ+ Youth. Issue 3 (2nd September 2017) - Chan, Christian D.
Abstract : There is an extensive need to explore the intersection of spirituality in conjunction with sexuality, gender identity, and affectional identity as a result of the nuanced complexity and paucity of conceptual and empirical literature in this area, which holds to a substantial diversity between and within identities. Furthering this exploration is the consistent dialogue of spirituality for the lesbian, gay, bisexual, transgender, and queer (LGBTQ+) community that offers context at-large and in heavy concentration in other areas of the life span, yet integrates far less into spirituality for youth and, more specifically, for LGBTQ+ youth. This article generates a conceptual framework derived from the ecological systems model and intersectionality theory to deliver insights relevant to addressing systemic barriers, practices, and complexities in attending to spirituality for LGBTQ+ youth.